The Spectator, 2016-03-03 - Spectator, Valdosta State University (Valdosta State University, 2016)
The Spectator, March 3, 2016. Vol. 90, No. 7. #ValTrumpsta -- (United States presidential election of 2016: Donald Trump Campaigns at Valdosta State University)
The Spectator: The Unfiltered, Uncensored Voice of the Students
Process by Valdosta State University Archives and Special Collections, 2016. Dallas Suttles, dasuttles@valdosta.edu. Scan date: 3/10/2016. OCR: ABBYY FineReader 11.0.
Keywords: Valdosta State University -- Periodicals